Evidence for associated production of a single top quark and W boson in pp collisions at sqrt[s]=7 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; et al. (2013)
Evidence is presented for the associated production of a single top quark and W boson in pp collisions at sqrt[s]=7  TeV with the CMS experiment at the LHC. The analyzed data correspond to an integrated luminosity of 4.9  fb(-1). The measurement is performed using events with two leptons and a jet originated from a b quark. A multivariate analysis based on kinematic properties is utilized to separate the tt background from the signal. The observed signal has a significance of 4.0σ and corresponds to a cross section of 16(-4)(+5)  pb, in agreement with the standard model expectation of 15.6±0.4(-1.2)(+1.0)  pb.